1985
DOI: 10.1002/j.1460-2075.1985.tb03766.x
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic type I topoisomerase is enriched in the nucleolus and catalytically active on ribosomal DNA.

Abstract: The distribution of eukaryotic DNA topoisomerase I in the cell has been analyzed at four levels: (i) at the level of the nuclear matrix; (ii) at the cytological level by immunofluorescence of whole cells; (iii) at the electron microscopic level using the protein A/colloidal gold technique; and (iv) at the level of DNA to identify in situ the sequence upon which topoisomerase I is catalytically active. Although topoisomerase I is clearly distributed non‐randomly in the nucleus, the unique distribution of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
99
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(112 citation statements)
references
References 41 publications
(34 reference statements)
13
99
0
Order By: Relevance
“…Also, our localization of the MRN proteins in human Purkinje neurons is completely consistent with the observations of Jacobsen et al [19]. With regard to TOP1, in addition to obtaining identical results using two independently generated monoclonal antibodies, our observation that TOP1 is localized to the nucleolus and nucleoplasm is consistent with other studies on the distribution of this enzyme within the nucleolus [23], and nucleus, including observations of GFP-tagged TOP1 in living human cells [24,25]. It should be noted that in one study [34], cytoplasmic TOP1 staining was observed in the mouse Purkinje neurons.…”
Section: The Mrn-complex and Topoisomerase I Are Also Concentrated Insupporting
confidence: 92%
See 2 more Smart Citations
“…Also, our localization of the MRN proteins in human Purkinje neurons is completely consistent with the observations of Jacobsen et al [19]. With regard to TOP1, in addition to obtaining identical results using two independently generated monoclonal antibodies, our observation that TOP1 is localized to the nucleolus and nucleoplasm is consistent with other studies on the distribution of this enzyme within the nucleolus [23], and nucleus, including observations of GFP-tagged TOP1 in living human cells [24,25]. It should be noted that in one study [34], cytoplasmic TOP1 staining was observed in the mouse Purkinje neurons.…”
Section: The Mrn-complex and Topoisomerase I Are Also Concentrated Insupporting
confidence: 92%
“…This pattern is consistent with other data showing that TOP1 is primarily localized to the nucleolus [23], but shuttles between the nucleolus and the nucleoplasm [24,25], and therefore provides further evidence of the specificity of staining. In some Purkinje neurons however, this pattern was reversed, with the amount of TOP1 being lower in the nucleolus than in the nucleoplasm ( Figure 5B, bottom row).…”
Section: Topoisomerase I Is Also Concentrated In the Nucleus Of Purkisupporting
confidence: 92%
See 1 more Smart Citation
“…Although their biological function is not completely defined , this class of topoisomerase has been implicated in transcriptional (Akrigg and Cook 1980;Dynan and Burgess 1981;Sternglanz et al 1981;Weisbrod 1982;Fleischmann et al 1984 ;Gilmour et al 1986;Shastry 1986) as well as in recombinational and replicational (Kikuchi and Nash 1979 ;Sternglanz et al 1981 ; also see Gellert 1981 ;Bullock et al 1985 ;Zeng et al 1985) events. J n higher eukaryotes topoisomerase I is enriched in the nucleolus (Fleischmann et al 1984;Muller et al 1985) and may play a role in transcription of supercoiled rDNA in vitro (Garg et al 1987). Studies in Tetrahymena indicate that the ribosomal DNA-associated enzyme…”
Section: Introductionmentioning
confidence: 99%
“…This catalytic intermediate creates single-strand DNA breaks, allowing the DNA molecule to rotate around the intact DNA strand at the cleavage site, leading to a relaxation of the DNA molecule, and in this way replication, transcription and other DNA functions can proceed. These enzyme-bridged breaks are then resealed by topoisomerase I (Champoux, 1976;Muller, 1985;Muller et al, 1985;Camilloni et al, 1989).…”
Section: G1147211mentioning
confidence: 99%